Ne jamais dire « Fontaine, je ne boirai pas de ton eau » - Virginie Prioux (Projets de Paysage)
Thinking that the many descriptions of landscapes surrounding the characters from the Rougon-Macquart are nothing more than a mere naturalist requirement would greatly reduce the scope of these pages. The gardens, parks and mostly the water points described have an obvious symbolic meaning in the novels: water jets, waterfalls and fountains appear at key moments and mirror the voluptuousness and the sensuality displayed by the protagonists. The gardens, may they be tempters, accomplices or witnesses to forbidden love affairs, take part in the intimacy of characters who find in the new Eden the basic instincts of the original sin.